Simulación de optimización de rutas disminuyendo la probabilidad de contagio de COVID-19 a través de CupCarbon (2020)
The pandemic generated by the new SARS VOC-2 virus has spread globally since the beginning of 2020 and has posed a new risk to global health. Currently, according to the World Health Organization, or as WHO is better known, it records a total of 42,906,084 confirmed cases of infection, 31,650,029 cases of recovery and 1,154,210 deaths globally as of October 24, 2020, and is an active problem until 2021 according to estimates by the organization [9]. Given that in cities like Bogotá there is overcrowding, there is a risk of contagion in the streets due to the crowding that can occur, and therefore a way to intervene and reduce the probability of contagion is to design routes that guide citizens to walk on streets where the probability of contagion is as low as possible. By means of a modeling system with the CupCarbon tool of events for spaces such as cities...